Penerapan Metode Weighted Product dalam Sistem Pendukung Keputusan Rekomendasi Pemilihan Jurusan Kuliah di Perguruan Tinggi - Suherman Halim; Geyza Falihy Putra Dini; Hendry Gunawan; Sunny Samsuni (Universitas Serang Raya, 2026)
Determining a college major is an important decision that students often make without objective consideration, risking a mismatch between interests and abilities, which can ultimately lead to changing majors or dropping out. This research aims to design and implement a web-based Decision Support System (DSS) capable of providing objective major recommendations by considering students' academic abilities. The Weighted Product (WP) method was chosen due to its capability in handling multi-criteria problems with proportional weighting and automatic normalization. The system was developed using a technology stack of PHP, MySQL, HTML, CSS, and JavaScript, with XAMPP as the local server. Data was collected from 30 students of grade XII Science program at SMAN 8 Kota Serang, covering scores from six subjects (Mathematics, English, Indonesian, Physics, Chemistry, Biology) and five alternative engineering majors (Electrical Engineering, Mechanical Engineering, Civil Engineering, Chemical Engineering, Informatics). Testing results show that the system can generate major recommendations in less than 2 seconds. Accuracy evaluation using blackbox testing and cross-validation between final grades and try-out scores resulted in a compatibility rate of 36.67% for recommendations based on try-out scores, which is statistically more accurate compared to final grade-based recommendations (with 63.33% incompatibility). These findings indicate that try-out data is more representative in predicting academic potential for university admission. This system has proven to be effective, efficient, and has significant potential to be adopted by educational institutions as a data-based counseling tool